How MNCs’ perceive and respond to the Polish institutional environment - Stępień, Beata (Economics and Business Review, 2006)
The article discusses the significance and role of institutional analysis in building up competitiveness of the economy and evaluates condition of the Polish institutional system from the viewpoint of foreign investors. It also analyses an impact of the Polish institutional environment on the status, structure and activities of MNCs operating in Poland. Preliminary results of empirical studies conducted by the author in 20 Polish manufacturing subsidiaries of MNCs are shown and discussed here. The paper begins with a short presentation of what institutions are, what constitutes an institutional environment and discusses the difficulty and importance of its appropriate creation. The next section is a short description of the main features of the Polish institutional environment. Analyses of some empirical data are in the last part of the paper; these concern opinions of MNCs about operating in Poland and information about their internal structure and organizational practices in comparison with analogous sister companies operating in other host markets. (original abstract)